2018
DOI: 10.1186/s12906-018-2267-9
|View full text |Cite
|
Sign up to set email alerts
|

10-hydroxy-2-decenoic acid of royal jelly exhibits bactericide and anti-inflammatory activity in human colon cancer cells

Abstract: BackgroundRoyal jelly (RJ), the exclusive food for the larva of queen honeybee, is regarded as the novel supplement to promote human health. The function of RJ may be attributed to its major and unique fatty acid, 10-hydroxy-2-decenoic acid (10-HDA). The current study investigated the anti-inflammory function of 10-HDA on human colon cancer cells, WiDr, as well as its effect on the growth of pathogenic bacterium.MethodsThe pro-inflammatory cytokines, receptor antagonist cytokine (IL-1ra) and nuclear factor-kap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 33 publications
3
75
0
4
Order By: Relevance
“…The linearity and limits of detection (LOD) and quantification (LOQ) were assessed. Solutions from 10 to 2000 ng/mL of 10-HDA, 10-hydroxydecanoic acid, 3-hydroxydecanoic acid, decanedioic acid and 2-dodecenedioic acid [3 replicates; 16 levels (10,30,50,80,100,200, 300, 400, 500, 600, 700, 800, 1000, 1300, 1500, 2000 ng/mL); n = 3 × 16] and solutions from 5-500 ng/mL of decanoic acid and dodecanoic acid were used for the construction of the linear curves [3 replicates; 8 levels (10, 30, 50, 100, 200, 300, 400, 500 ng/mL); n = 3 × 8]. The instrumental detection limits were estimated (LOD = 3.3 * Sa/b, where Sa is the standard deviation of the response of six replicates of the lowest standard and b is the slope of the calibration curve).…”
Section: Methods Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…The linearity and limits of detection (LOD) and quantification (LOQ) were assessed. Solutions from 10 to 2000 ng/mL of 10-HDA, 10-hydroxydecanoic acid, 3-hydroxydecanoic acid, decanedioic acid and 2-dodecenedioic acid [3 replicates; 16 levels (10,30,50,80,100,200, 300, 400, 500, 600, 700, 800, 1000, 1300, 1500, 2000 ng/mL); n = 3 × 16] and solutions from 5-500 ng/mL of decanoic acid and dodecanoic acid were used for the construction of the linear curves [3 replicates; 8 levels (10, 30, 50, 100, 200, 300, 400, 500 ng/mL); n = 3 × 8]. The instrumental detection limits were estimated (LOD = 3.3 * Sa/b, where Sa is the standard deviation of the response of six replicates of the lowest standard and b is the slope of the calibration curve).…”
Section: Methods Validationmentioning
confidence: 99%
“…As described in the introduction, the unusual free fatty acids of RJ have been shown to exhibit a variety of bioactivities such as antimicrobial, anti-inflammatory, immunomodulatory, and growth promoting activities [5][6][7][8][9][10][11]. However, no attention has been paid so far on the potential interactions of RJ fatty acids with free fatty acid receptors.…”
Section: Biological Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Some of the RJ proteins such as major royal jelly proteins (MRJPs) (Mairesse et al 1998), jelleines (Fontana et al 2004), and royalisin (Fujiwara et al 1990) are reported to have properties of antimicrobial, antifungal, anti-tumor, anti-diabetic, and anti-hypertensive activities (Bíliková et al 2001;Oka et al 2001;Tokunaga et al 2004). In addition, RJ regulates inflammation, oxidative stress, and vasodilation activity (Okamoto et al 2003;Liu et al 2008;Nakajima et al 2009;Kolayli et al 2016;Yang et al 2018). These RJ-induced activities are widely believed to help maintain homeostasis and recover from pathological conditions; therefore, RJ has been used as a cosmetic, health food, or dietary supplement (Ramadan and Al-Ghamdi 2012;Cornara et al 2017;Yoneshiro et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it was speculated that RJ prolongs the lifespan of the queen honeybee relative to worker honeybees [ 7 ]. (2) RJ can modulate inflammation, oxidative stress and vasodilatory activity [ 8 , 9 , 10 , 11 , 12 ]. These RJ-induced activities are widely considered to be useful to maintain homeostasis and recover from pathological conditions; therefore, RJ has been used as cosmetics, health food, or dietary supplement [ 13 , 14 ], (3) RJ affects the immune system under various physiological and pathological conditions, including malignancies and stimulate not only immunocompetent cells but also antibody production [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%